Changing social norms: The impact of normative feedback included in motivational enhancement therapy on cannabis outcomes among heavy-using adolescents. (January 2018) - Blevins, Claire E.; Walker, Denise D.; Stephens, Robert S.; Banes, Kelsey E.; Roffman, Roger A.
Abstract: Introduction: Heavy cannabis use is a problematic behavior, particularly among some adolescents. Adolescents are particularly prone to social influence. As such, injunctive norms (perceptions of others' approval of cannabis use) and descriptive norms (perception of frequency of others' cannabis use) influence cannabis behavior. Given that norms are not always accurate, motivational enhancement therapy aims to reduce cannabis use through normative feedback and correction of normative misconceptions. The purpose of this study was to evaluate the relationships between perceived norms (descriptive and injunctive) and cannabis-related outcomes (use, cannabis-related problems, and cannabis use disorder symptoms) in a heavy cannabis-using adolescent population receiving motivational enhancement therapy. Methods: Heavy cannabis-using individuals (n = 252, 68% male, mean age 13.38, 59% Caucasian) were recruited from six Seattle high schools for a motivational enhancement therapy-based intervention involving normative feedback. Results: Participants perceived higher rates of cannabis use among close friends than other same age teens and reported a higher perception of approval for cannabis use from close friends as compared to perceived approval of other same aged peers. Personal approval and the perceived approval of other same age teens were reduced following the intervention but there was no evidence of change in normative perceptions for close friends following the normative feedback interventions. Changes in normative perceptions were related to decreases in cannabis use and -related outcomes. Conclusions: Results suggest the importance of normative feedback in changing behavior in adolescent cannabis users, but also highlight the ongoing influence of close friends. Highlights: Perceived norms of close friends versus other same-aged teens significantly differed. Norms changed over time after engagement in motivational enhancement therapy. Changes in norms were associated with changes in cannabis outcomes.